After Neoliberalism - John Quiggin (ANU Press, 2024)
Since the early 1980s, Australian economic policy has been dominated by the ideology of neoliberalism (also known as 'economic rationalism'), including policies of privatisation, financial deregulation and micro-economic reform. Throughout this period, John Quiggin has presented critical assessments of neoliberal policies and the claims about productivity growth made in support of those policies. The credibility of neoliberalism was fatally wounded by the Global Financial Crisis and its aftermath. Nevertheless, market ideology has lumbered on in zombie form, for want of a clear alternative. It is only recently that we have begun to reverse the failed policies of privatisation and deregulation and to consider radical alternatives such as a shift to a four-day week. This book provides a historical perspective in the form of a series of articles written from the mid-1980s to the present day. It concludes with some suggestions for the way forward, after neoliberalism.
Keywords: 330; neoliberalism; privatisation; microeconomic; reform; productivity; universal basic income